High Penetration PV in Distribution Networks, Design and Control - Ashkan Mohammadi; Saman Hosseini Hemati (Indonesian Journal of Electrical Engineering and Computer Science, 2016)
Global warming is a direct consequence of consumption of fossil fuels which emit greenhouse gasses as they produce energy. Solar energy is the most available energy throughout the world in which regardless of capital investment is free and most importantly clean and emission free and could be a solution for global warming along with other renewable sources of energy. But as photovoltaic energy is becoming widespread and penetration level of photovoltaic power plants increase, several issues rise in distribution networks. In this paper, a high penetration photovoltaic power plant is designed and issues associated with it are thoroughly discussed. Voltage rise and cloud passage effect are amongst the most challenging issues in design and implementation of a high penetration photovoltaic power plant in distribution networks. Transient effects of cloud passage could lead to unacceptably low voltage in Point of Common Coupling and maximum penetration level must be set according to these issues. An efficient Maximum Power Point Tracking (MPPT) and a DC link voltage control scheme are also presented. Simulations have been done in Matlab/Simulink environment.